Critical state characteristics of lateritic soils treated with rice husk ash as subgrade soil - Chibundu Enyinnia; Ugochukwu Okonkwo; Chidobere Nwa-David (Engineering and Technology Journal)
The behavior of subgrade materials plays a pivotal role in determining the longevity of transportation infrastructure. More often, interests had been focused on the mechanical behavior of treated soils prior to the failure stage, while the critical state conditions had received very little attention. This study focused on the critical state characteristics of two distinct lateritic soils (Sample 1, non-plastic and Sample 2, plastic) which were treated with rice husk ash (RHA). The chemical composition of the rice husk ash was examined using X-ray fluorescence. The two natural soils were characterized, and the X-ray diffraction technique was used to identify the soil minerals. The lateritic soils were subjected to varying percentages of rice husk ash treatment, which ranged from 0-21% at 3% intervals. The experiments on treated soils were compaction, California bearing ratio (CBR), and shear strength test. For both samples, the maximum dry density was reduced while the optimum moisture content increased with the addition of RHA from 0-21%. The maximum deviator stress attained values of 941.8k N/m2   and 769.06 kN/m2   at the application of 9% and 12% RHA for Samples 1 and 2, respectively. The CBR of Sample 1 was reduced by 81% with the addition of 21% RHA, while that of Sample 2 increased by 14.22% with the addition of 6% rice husk ash. The critical state parameter (M) for Sample 1 increased by 5.08% at the addition of 9% RHA, while that of Sample 2 increased by 13.09% at 12% RHA. The values are in the same range with some granular and unsaturated soils.